Research and prototyping methods of steganography using mosaic - Pevnev, Volodymyr; Voikov, Yurii (Національний технічний університет "Харківський політехнічний інститут", 2020)
The paper considers the possibility of using a mosaic composed of many miniature images to hide the fact of text information transmission. The results of the study of optimal mosaic construction when using steganographic methods of hiding information are presented. The use of the proposed algorithms implies the use of сryptographically secure pseudorandom number generator with dynamically changing parameters for concealing information. The generators are used to determine the location of information bits in a certain mini-images, as well as in a specific pixels and color channels. Using the proposed algorithm, no more than twenty-five percent of the color channels are changed, provided that one bit per color is used. This paper is supplemented with illustrations and examples of how the algorithm works.

Запропонована система дозволяє приховано передавати інформацію в мозаїці, а також володіє достатньою захищеністю для захисту інформації від несанкціонованого читання в випадки виявлення факту передачі інформації. У поєднанні з даним підходом можна використовувати додатково будь-який алгоритм шифрування для забезпечення ще більшої захищеності даних. Представлений алгоритм кодування і приховування даних можна легко адаптувати для роботи зі звичайними растровими зображеннями, звуковими файлами та іншими типами даних, які представлені у вигляді масиву значень.
Дослідження та прототипирування методів стеганографії з використанням мозаїки
Keywords: pseudo-random sequence generators; pixel; color channel; information bit; генератор псевдо-випадкової послідовності; піксель; канал кольору; інформаційний біт